Pengaruh Konsentrasi Tepung Beras Ketan Terhadap Mutu Dodol Pepaya - Dorina Kelmaskosu; Rachel Breemer; Febby J Polnaya (Universitas Pattimura, 2015)
The objective of this research was to determine the best level of concentration of waxy rice flour on the quality of â€œdodolâ€ papaya. A completely randomized experimental design having of five levels of treatment, namely: control, waxy rice concentration of 0, 10, 20, 30, and 40% were applied in this research. Variables measured on the product including the chemical composition (moisture, ash, vitamin C, and reducing sugar content) and the products were also subjected to organoleptic test for springiness, taste, color, odor, and preference level. The results showed that the different waxy rice flour concentrations had significant effects over variables measured. The waxy rice flour with the concentrations of 10% produce the â€œdodolâ€ papaya with the best quality.